ANALISIS TERHADAP KOMODIFIKASI TUBUH PEREMPUAN DALAM IKLAN ES KRIM MAGNUM VERSI PINK & BLACK - Susanti, Dede; Rochman, Kholil Lur (Fakultas Dakwah IAIN Purwokerto, 2016)
The womanâ€™s body in the advertising world today used as a commodity in the public interest. In the space of capitalism, women became a profitable commodity handful of parties. In the world of advertising, women became an object to conquer the commercial market. â€œBodyâ€ and the expression of women explored massif to give the impression that support a variety of image ads. Researchers chose Magnum ice cream ad version of Pink and Black as advertisements analyzed because the message conveyed in these ads are more creative and taking pictures with the reversal of the model in repeated up to three times this can build imagination in sex. This research was conducted through qualitative approach with descriptive research. Source of the data obtained is Video ads Magnum ice cream Pink and Black, the production of PT (Walls) Unilever. In addition, data obtained also from official data: books, journals, papers, articles, and research results preexisting relevant to this study. The theory used in this research is the theory of Marxism commodification. Results The study confirmed that the female body attractiveness is always used as a commodity which is able to accumulate capital or generate profits. Because the woman is a very big market in the media industry which is believed to strengthen the advertising message. The concept of commodification in the ad Magnum ice cream version of Pink and Black itself is using her sex appeal with the intention to attract public attention to generate suggestions sexual show some fragments of the bodyâ€™s vital to be â€˜exclusiveâ€™ shown by visualization of the reversal of the model is carried out three times in playback ads. As well as other forms of commodification that is the commodification of content wherethe content / message in the form of sexual material and includes images of the model with a sensual pose, commodification audiences in this ad arepeople who consume products produced by media. And lastly commodification of workers who could hire them in the activities of production and distribution by the capital owners.Â Tubuh perempuan dalam dunia periklanan masa kini dijadikan sebagai komoditas dalam menarik perhatian publik. Dalam ruang kapitalisme, perempuan menjadi komoditas yang menguntungkan segelintir pihak. Di jagat iklan, perempuan menjadi objek untuk menaklukkan pasar komersial. â€œTubuhâ€ dan ekspresi perempuan dieksplorasi secara massif untuk memberi berbagai kesan yang mendukung citra iklan. Peneliti memilih iklan es krim Magnum versi Pink and Black sebagai iklan yang dianalisis karena pesan yang disampaikan dalam iklan tersebut lebih kreatif dan terdapat pengambilan gambar dengan penjungkirbalikan sang model yang di ulang sampai tiga kali ini dapat membangun imajinasi dalam seks. Penelitian ini dilakukan melalui pendekatan kualitatif dengan jenis penelitian deskriptif. Sumber data yang diperoleh adalah Video iklan es krim Magnum Pink and Black, produksi PT (Walls) Unilever. Selain itu, data yang diperoleh juga dari data resmi: buku, jurnal, makalah, artikel, dan hasil penelitian yang sudah ada sebelumnya yang relevan dengan penelitian ini. Adapun teori yang digunakan dalam penelitian ini adalah teori komodifikasi Marxisme. Hasil penelitian ini menegaskan bahwa kemolekan tubuh perempuan selalu dijadikan komoditas yang mampu mengakumulasi modal atau menghasilkan keuntungan. Karena perempuan adalah pasar yang sangat besar dalam industri media yang dipercaya mampu menguatkan pesan iklan. Konsep komodifikasi dalam iklan es krim Magnum versi Pink and Black ini sendiri yaitu menggunakan daya tarik seks dengan maksud menarik perhatiankhalayak.